The real Dada Mother Goose : a treasury of complete nonsense - Scieszka, Jon (Candlewick Press, 2022)
Draws on Dadaism's rejection of reason and rational thinking to retell six classic nursery rhymes. Reimagines the rhymes as a recipe, a map, a joke, and a newspaper article; recites the rhymes in Morse code, reverse, and Esperanto; and writes them in hieroglyphs, anagrams, military alphabet, rebus style, musical notation, a crossword puzzle, and haiku.